Enabling the internet of things : fundamentals, design, and applications - Iqbal, Muhammad Azhar; Hussain, Sajjad; Huanlai, Xing.; Imran, Muhammad Ali. (b)
"In the modern era, a plethora of things is being connected to each other using underlying network technologies with an aim to promote the paradigm of Internet of Things (IoT). IoT comprises of diversified technologies including pervasive computing, sensor technology, embedded systems, communication technologies, sensor networking, Internet protocols etc. IoT also benefits the economic growth of civilized societies. The objective of this book is to provide a good starting point to understand the fundamentals and design of IoT systems. Moreover, it is an effort to partially fill the gap associated with the understanding of IoT concepts through programming in an abstract way. Topics covered include IoT fundamentals, IoT hardware/software components, IoT protocol stack, security, IoT applications and their implementations, challenges, their possible solutions and future directions. Moreover, social aspects of smart things are also discussed"-- |c Provided by publisher.
Includes references and index.
Keywords: Internet of things